The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.36263/nijest.2021.01.0260
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Linear Combination Procedures with GIS and Remote Sensing in Flood Vulnerability Analysis of Abeokuta Metropolis in Nigeria

Abstract: The study offered the opportunity for an evaluation of the role of Remote Sensing and Geospatial techniques in flood disaster risk management and development of spatial decision support system for flood risk assessment and management in Abeokuta metropolis. Datasets used includes cloud free high resolution satellite images and Shuttle Radar Topographic Mission (SRTM) data downloaded from earth explorer site. Soil data used was obtained from Food and Agriculture Organization (FAO’s) Harmonised World Soil Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…The subbasins with less temporal runoff difference were relatively less disturbed (sub-basin W820) than the sub-basins with obvious temporal runoff differences, suggesting that built-up areas recorded more discharges than the less disturbed regions. An evaluation of land use/land cover changes around the Ogun River basin within the study period has suggested a steeper hydrograph in 2018 than in 2010; a condition that points at increased propensity to floods in a later period (see, e.g., Adelekan, 2011;Oyedepo et al, 2021).…”
Section: Changes In Average Runoff Conditionmentioning
confidence: 99%
“…The subbasins with less temporal runoff difference were relatively less disturbed (sub-basin W820) than the sub-basins with obvious temporal runoff differences, suggesting that built-up areas recorded more discharges than the less disturbed regions. An evaluation of land use/land cover changes around the Ogun River basin within the study period has suggested a steeper hydrograph in 2018 than in 2010; a condition that points at increased propensity to floods in a later period (see, e.g., Adelekan, 2011;Oyedepo et al, 2021).…”
Section: Changes In Average Runoff Conditionmentioning
confidence: 99%
“…Dengan menganalisis berbagai kriteria seperti curah hujan, topografi, penggunaan lahan, dan sebagainya, MCA dapat membantu menentukan variabel-variabel yang paling berpengaruh dalam menyebabkan banjir. Oyedepo et al, (2021) berpendapat bahwa MCA dapat membantu mengintegrasikan berbagai perspektif dalam analisis banjir. Karena banjir mempengaruhi berbagai aspek kehidupan, seperti kesehatan, ekonomi, dan lingkungan, MCA dapat membantu menggabungkan berbagai perspektif dan kepentingan dalam proses pengambilan keputusan.…”
Section: Pendahuluanunclassified
“…Abeokuta, the capital of Ogun State in the southwest, depicts a typical developing urban city in Nigeria. The city spreads across ve Local Government areas (Abeokuta North, Abeokuta South, Obafemi Owode, Ewekoro, and Odeda) with a population of 593,140 (Oyedepo et al, 2021). Abeokuta enjoys a tropical climate, distinct wet and dry seasons, and a dry to a wet period of about 130 to 200 days.…”
Section: The Context and Study Areamentioning
confidence: 99%